Infrastructures as Ontological Experiments - Casper Bruun Jensen; Atsuro Morita (Engaging Science, Technology, and Society, 2015)
Ontology has recently gained renewed attention in science and technology studies and anthropology (e.g. Gad, Jensen and Winthereik 2015; Holbraad, Pedersen and Viveiros de Castro 2014; Woolgar and Lezaun 2013). Yet, it has a considerably longer pedigree than these recent debates might lead one to think. Experiments, of course, have long held the attention of sociologists, historians, and philosophers of science (Collins 1985; Gooding 1990; Shapin and Schaffer 1985). And infrastructures have been the focus of sustained inquiry in the sociology and history of technology (Bowker 1994; Hughes 1983). Once these terms are put into conjunction, however, each gets a somewhat different inflection. The following note briefly explores the conceptual purchase of considering infrastructures as ontological experiments.